The Effect of the Problem-Based Learning (PBL) Model Assisted by Vidumath Media on the Critical Thinking Skills of Fourth-Grade Elementary School Students - Putri Nimaturrohmah Nisa'i; Hesti Yunitiara Rizqi (Darul Yasin Al Sys, 2026)
Problem-Based Learning (PBL) is widely employed to strengthen students’ critical thinking; however, empirical research on its integration with Vidumath media in elementary mathematics education remains limited. This study aimed to examine the effect of Vidumath-assisted PBL on the critical thinking skills of fourth-grade elementary school students. A quantitative quasi-experimental approach with a nonequivalent control group design was employed, involving 51 fourth-grade students from SD Negeri Klepu 01 and SD Negeri Klepu 02 who were selected using a non-random sampling approach. The experimental group comprised 26 students, while the control group consisted of 25 students. Data were collected through critical thinking tests, observation sheets, and questionnaires and analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s homogeneity test, and an independent-samples t test. The findings indicate that students taught through Vidumath-assisted PBL demonstrated significantly higher critical thinking skills than those who received conventional instruction. The experimental group achieved a mean post-test score of 81.38, compared with 68.60 in the control group, with the difference being statistically significant (p < .001). These findings confirm that integrating PBL with Vidumath media can facilitate active, meaningful, and student-centered mathematics learning while strengthening students’ higher-order thinking skills. The study contributes to constructivist learning research by providing empirical evidence of the effectiveness of combining problem-based instruction with digital learning media in elementary mathematics education. Practically, the findings provide a reference for elementary school teachers seeking to implement innovative instructional strategies to enhance students’ critical thinking skills. Further research should examine the implementation of Vidumath-assisted PBL across different educational levels, subject areas, and learning contexts.